A közszféra és a vállalatok közötti bérátterjedések Magyarországon - Álmos Telegdy (Hungarian Academy of Sciences, Institute of Economics, Centre for Economic and Regional Studies, 2013)
– I identify wage spillovers from the public to the corporate sector with the help of a large public sector wage increase, which raised public sector wages by 40 percent in two years time, changing the average public relative wage from a fallback of 10.5 percent to a 12.5 percent premium. The spillover effect is identified with along the variation of the share of public sector employment along gender, experience and occupation. The analysis shows that 10 percent higher share of public sector workers within worker-type increases corporate wages by 1.5 percent. The spillover effect is positively correlated with the public wage premium, with low corporate wages, with occupations which are abundant in the public sector, and services. It is also larger in labor market cells where there is a large number of vacancies in the public sector as well as for corporate workers hired after the wage increase.
Keywords: J31; J45; 330; public sector; wage spillower; Hungary; Vergütungssystem im öffentlichen Dienst; Spillover-Effekt; Ungarn